Trusted Systems 6th International Conference, INTRUST 2014, Beijing, China, December 16-17, 2014, Revised Selected Papers - Yung, Moti.; Zhu, Liehuang; Yang, Yanjiang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Normal 0 false false false EN-US X-NONE X-NONE This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Conference on Trusted Systems, INTRUST 2014, held in Beijing, China, in December 2014. The conference brings together academic and industrial researchers, designers, and implementers with end-users of trusted systems, in order to foster the exchange of ideas in this challenging and fruitful area. The revised full papers focus on the theory, technologies and applications of trusted systems and cover all aspects of trusted computing systems, including trusted modules, platforms, networks, services and applications, from their fundamental features and functionalities to design principles, architecture and implementation technologies. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}.
Signature and authentication -- Secure protocols and access control -- Cloud security -- cryptographic aspects -- Software security -- Security analysis -- Secure communication and privacy.
Keywords: Computer science; Computer communication systems; Operating systems (Computers).; Computer security; Data encryption (Computer science).; Computer science -- Mathematics; Management information systems; Computer Science; Systems and Data Security; Data Encryption; Operating Systems; Computer Communication Networks; Management of Computing and Information Systems; Discrete Mathematics in Computer Science; Electronic books